Assessing the Risk of Groundwater Contamination from Pesticide Storage & Handling - Hickman, John S.; Kuhlman, Dennis K.; Hess, Larry G. (My University, 1998)
A step by step through pesticide storage and disposal practices to determine safe and effective storage and handling practices.
EP43_1998-08
Keywords: EP43; Environment and Natural Resources; Equipment and Structures; Health and Safety; EP